Bacterial colonisation of humidifier attachments on oxygen concentrators prescribed for long term oxygen therapy: a district review. Issue 4 (April 1991) - Pendleton, N; Cheesbrough, J S; Walshaw, M J; Hind, C R
Abstract : A microbiological survey was undertaken on the eight patients in the Liverpool District who have a humidifier attachment on their oxygen concentrator. All but one of the humidifiers were contaminated with potentially pathogenic bacteria.